Medicines and vaccines supply chains challenges in Nigeria: a scoping review - Olutuase, V.O.; Iwu-Jaja, C.J.; Akuoko, C.P.; Adewuyi, Emmanuel; Khanal, V. (2022)
Background: Medicines and vaccines supply chains represent critical systems for realising one of the major targets of the United Nations’ third Sustainable Development Goals (SDGs)—access to safe, effective, quality, and affordable essential medicines and vaccines, for all. However, evidence suggests the system is confronted with several challenges in many low-medium income countries, including Nigeria. This scoping review aims to summarize the available evidence on the challenges of medicines and vaccines supply chain system in Nigeria. Results: We searched relevant databases including Scopus and Web of Science for studies published between January 2005 and August 2020 on the challenges associated with medicines and vaccines supply chain systems in Nigeria. Our findings implicate several factors including difficulty with medicines or vaccines selection, procurement, distribution, and inventory management. Others included poor storage infrastructure, financial constraints, insecurity, transportation challenges, inadequate human resources, weak, or poorly implemented policies. These challenges mostly resulted in stock-outs of essential medicines which notably got worsened during the current COVID-19 pandemic. Conclusion: Our study is a wake-up call on the need to prioritise the critical sector of the supply chain systems for medicines and vaccines in Nigeria. Effective implementation of existing policies, improved security, strengthening of the health system through adequate budgetary allocations, and provision of infrastructure including regular availability of electricity are keys to surmounting the challenges and improving access to medicines or vaccines in Nigeria.